Internet of Things with Wireless Sensor Network Potential Business Possibility - Dhanang Kusuma Wardhana (Department of Electrical Engineering, 2020)
Wireless Sensor Network is an exciting part of the Internet of Things to study because of its versatility in various types of industries. The existence of wireless sensor networks is believed to develop similar to the evolution of computer network systems when they were first connected and eventually became what we call today the Internet (World Wide Web). The source of information from the wireless sensor network will be more precious than the current internet information source, and this will change the World Wide Web to what is called the World Wide Sensor Network (WWSN). This paper focuses on the impact of this transformation process, the parties involved, the operational and business models possibility.